A Study on Factors Affecting Customer Satisfaction a Case Study of Hotel X - Shi, Guanhong; Nualnoom, Pairote (Science, Technology, and Social Sciences Procedia, 2022)
With the continuous increase of Gross Domestic Products per capita of consumers in China, the domestic consumption market gradually presents the trend of rationalization and personalization, which puts forward new requirements for hotel products and services. In recent years, people are more willing to choose high-quality hotel products. In addition, foreign chain hotels have gradually penetrated the domestic market, and the increasing number of competitors has made domestic hotels fight price wars and have no intention to create personalized services, resulting in no difference in hotel services and the trend of popular business model. This development trend will reduce the profit of the hotel and is not conducive to the development of the hotel. Only by improving the quality of the hotel and improving the customer satisfaction, can we meet the needs of customers and promote the healthy development of the hotel. Therefore, this paper takes Hotel X as the research object, combined with the relevant research of customer satisfaction, based on the actual survey data, to study its customer satisfaction. This study adopts the method of sampling survey, and the customer groups cover students, organization/institution staff, domestic enterprise personnel, freelancers, foreign enterprise personnel, teachers and other groups, so that the collected data fully conforms to the structural characteristics of hotel accommodation groups, making the conclusion of the study more convincing. Based on the survey data of Hotel X, this paper analyzes the operation status of Hotel X. Considering the impact of customer perceived value and customer expectation on customer satisfaction, the influencing factors of customer satisfaction of Hotel X are determined. The results show that the average score of customer satisfaction to Hotel X is above average, which has a large room for improvement. Hotel X should create some characteristic and innovative services or products to meet the customer’s perceived value and improve customer satisfaction. Based on the results of the survey and analysis, this paper puts forward some targeted strategies and suggestions to improve the customer satisfaction of Hotel X, which lays a theoretical foundation for the management of Hotel X to formulate relevant measures on customer satisfaction.